1996
DOI: 10.1016/0272-6963(95)00041-0
|View full text |Cite
|
Sign up to set email alerts
|

The operations management role in hospital strategic planning

Abstract: Although there is a wealth of research on operations management and strategic planning in hospitals, there has been little if any research on the integration of these two issues. Hospital administrators are being pressured to improve the quality of services and to curb costs -two primary themes within the field of operations management. This leads us to wonder to what extent operations are considered within the strategic planning process and what impact it may have. By surveying the literature, we identify a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 56 publications
1
60
0
2
Order By: Relevance
“…Zelman and Parham (1990) characterise four strategies hospitals use to define their business focus (i.e., generalist, market specialist, service specialist, or super specialist). Recognising that each business can undertake a strategic orientation, Butler et al (1996) also synthesise Miles and Snow's (1978) pattern with hospital-specific strategic orientations: pacesetter hospitals are at the forefront of medical knowledge and technology, pacemaker hospitals are at (or near) the 3 According to this framework, firms have two strategic priorities, representing two extreme points on a spectrum: low cost production to be a cost leader or superior product quality, flexibility, customer service, delivery, and design to achieve differentiation leadership (Chenhall and Langfield-Smith, 1998 According to organisation theory (Diesing, 1962;Quinn and Rohrbaugh, 1983;Smith et al, 1985), priorities are organisational concerns that can be observed by focusing on the organisational attention and resources deployed. Smith et al (1985) argue that authors drawing on this theory usually describe very similar typologies of priority, typically containing a rational goal category (i.e., planning and setting organisational goals for improved productivity and efficiency), an internal process category (i.e., coordinating and distributing information and communication for stability and security), an open system category (i.e., developing flexibility and readiness for resources acquisition and external support), and a political support category (i.e., maintaining cohesion and morale for a better human resources development).…”
Section: Hospital Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Zelman and Parham (1990) characterise four strategies hospitals use to define their business focus (i.e., generalist, market specialist, service specialist, or super specialist). Recognising that each business can undertake a strategic orientation, Butler et al (1996) also synthesise Miles and Snow's (1978) pattern with hospital-specific strategic orientations: pacesetter hospitals are at the forefront of medical knowledge and technology, pacemaker hospitals are at (or near) the 3 According to this framework, firms have two strategic priorities, representing two extreme points on a spectrum: low cost production to be a cost leader or superior product quality, flexibility, customer service, delivery, and design to achieve differentiation leadership (Chenhall and Langfield-Smith, 1998 According to organisation theory (Diesing, 1962;Quinn and Rohrbaugh, 1983;Smith et al, 1985), priorities are organisational concerns that can be observed by focusing on the organisational attention and resources deployed. Smith et al (1985) argue that authors drawing on this theory usually describe very similar typologies of priority, typically containing a rational goal category (i.e., planning and setting organisational goals for improved productivity and efficiency), an internal process category (i.e., coordinating and distributing information and communication for stability and security), an open system category (i.e., developing flexibility and readiness for resources acquisition and external support), and a political support category (i.e., maintaining cohesion and morale for a better human resources development).…”
Section: Hospital Strategymentioning
confidence: 99%
“…Zelman and Parham (1990) characterise four strategies hospitals use to define their business focus (i.e., generalist, market specialist, service specialist, or super specialist). Recognising that each business can undertake a strategic orientation, Butler et al (1996) also synthesise Miles and Snow's (1978) pattern with hospital-specific strategic orientations: pacesetter hospitals are at the forefront of medical knowledge and technology, pacemaker hospitals are at (or near) the state of the art in every department offered, and provider hospitals are usually small and emphasise operations management and cost control as key to their competitive strategy.…”
Section: Hospital Strategymentioning
confidence: 99%
“…(Bloom et al 2009). The health care industry can draw upon a vast range of management practices originally developed for the manufacturing and/or service sector to achieve better performance in the changing health care environment (Butler et al, 1996;Trisolini, 2002;Laing and Shiroyama, 1995). However, transferring and adapting best practices to the health care context is challenging as it not only involves understanding the technical components of health care, but also the operational, strategic, and human factors associated with its effective implementation (Berta and Baker, 2004), and the subsequent impact it can have on performance monitoring (Hood & Peters, 2004).…”
Section: Bloom and Colleagues (2009) In Conjunction Withmentioning
confidence: 99%
“…It reflects the natural process of increasing disaggregation in decision making as time progresses, and more information becomes available [534]. It also reflects the hierarchical (department) structure of most organizations [78]. Many MPC frameworks use the hierarchical decomposition into a strategic, tactical, and operational level, as first done by Anthony in 1965 [9].…”
Section: Literaturementioning
confidence: 99%
“…The performance, which is measured at an operational level, is the result of how well the various hierarchical planning activities are integrated. In [78], the authors indicate that the literature neglects cooperation between different managerial areas at the strategic level of hospital planning and control. They argue that to attain exceptional operational performance, it is important that the hospital's strategy consistently and coherently integrates operations issues from areas like Finance, Marketing, Operations, and Human Resources.…”
Section: Literaturementioning
confidence: 99%